Community social support and onset of dementia in older Japanese individuals: a multilevel analysis using the JAGES cohort data. Issue 6 (3rd June 2021) - Miyaguni, Yasuhiro; Tabuchi, Takahiro; Aida, Jun; Saito, Masashige; Tsuji, Taishi; Sasaki, Yuri; Kondo, Katsunori
Abstract : Objective: Recently, there has been an increase in the number of people with dementia. However, no study has examined the association between community-level social support and the onset of incident dementia using multilevel survival analysis. Design: A prospective cohort study. Participants and setting: We analysed data pertaining to 15 313 (7381 men and 7932 women) community-dwelling adults aged 65 years or older who had not accessed long-term care insurance and were living in Aichi Prefecture (seven municipalities) in Japan. Primary and secondary outcome measures: The association between community-level social support and onset of incident dementia was examined using the Japan Gerontological Evaluation Study, a prospective cohort study introduced in Japan in 2003. Incident dementia was assessed using Long-term Care Insurance records spanning 3436 days from the baseline survey. Results: During the 10-year follow-up, the onset of incident dementia occurred in 1776 adults. Among older people, a 1% increase in community-level social support (in the form of receiving emotional support) was associated with an approximately 4% reduction in the risk of developing dementia, regardless of socio-demographic variables and health conditions (HR=0.96; 95% CI=0.94 to 0.99). Conclusions: Receiving community-level social support in the form of emotional support is associated with a lower risk of developing incident dementia.